Output Signal Characteristics of a Post-detection EGC Combiner with Two ASK Input Signals in the Presence of Fading and Gaussian Noise - Banđur, Đ. V.; Banđur, M. V.; Stefanović, M. Č. (Elektronika ir Elektrotechnika, 2008)
The output signal of a noncoherent dual branch receiver with EGC combiner in presence of Nakagami fading and additive white Gaussian noise will be considered in this paper. The PDF of the receiver branch signal as well as the PDF of the EGC combiner output signal will be calculated and displayed in this paper. The mentioned probability density functions will provide an necessary assumption for determination of the other important receiver characteristics and parameters. Ill. 6, bibl. 5 (in English; summaries in English, Russian and Lithuanian).